KONSENTRASI HAMBAT DAN BUNUH MINIMUM EKSTRAK ETANOL DAN METANOL KULIT DURIAN (Durio zibethinus Murr) TERHADAP SALMONELLA THYPI - Rosellynia Calyptranti; Eva Luviriani; Linda Safitri (HERBAPHARMA : Journal of Herb Farmacological, 2022)
Durian (Durio zibethinus Murr) is a type of fruit that is very popular by everyone and is classified as a very abundant fruit. Compound content active in durian skin (Durio zibethinus Murr) such as alkaloids, phenols, flavonoids, tannins, and saponins can inhibit and kill bacteria that function as the antibacterial. The active compound can be obtained through the extraction process with a suitable solvent. This study aims to determine the value and difference between Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Durian Skin ((Durio zibethinus Murr.) Ethanol and Methanol Extract against Salmonella typhi. Salmonella typhi is a pathogenic bacterium that causes a large number of infections in humans in the form of typhoid fever. This study uses a completely randomized design (CDR). A factorial pattern consisting of 2 factors, namely the solvent factor and the concentration factor. Data analysis used Two Way ANOVA test to find out the comparison of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Durian Skin (Durio zibethinus Murr.) Ethanol and Methanol Extract against Salmonella typhi. If the data is not normally distributed then followed by a nonparametric statistical test, namely the Kruskal-Wallis test. The result of this study showed that at multilevel dilutions of Salmonella typhi which shows the number of colonies 30-300 CFU/ml at a dilution of 10-7. Durian peel ethanol extract can inhibit Salmonella typhi bacteria in the concentration of 25% and durian peel methanol extract can inhibit bacteria Salmonella typhi at a concentration of 10%. Statistical test results show that there is no difference in the Minimum Inhibitory Concentration (MIC) of Durian Skin ((Durio zibethinus Murr.) Ethanol and Methanol Extract against Salmonella typhi. (Asymp sig. >0,05).